The Iraqi quest for autonomy through military and diplomatic interventions, 1968-2003 - Tietzen, Katelyn Karly (Kansas State University, 2019)
This dissertation views the period of the Cold War and beyond through the eyes of Iraqi leaders, thanks to both the collections of the Conflict Records Research Center and the Baʿthist regime documents now housed at Stanford University. This study not only shows the complexity of how the tensions between the United States and the Soviet Union affected the Middle East; it also reveals how local and regional political, diplomatic, and military conditions played a crucial role in Iraq’s foreign policy initiatives and in its domestic security as well both before and after the fall of the Soviet Union in 1991. This work focuses on Iraqi foreign policy from 1968 through 2003. During this time period, the tension between the United States and the Soviet Union was intense and preoccupying—to them but not necessarily to all countries with whom they interacted. Various of those countries had their own agenda to pursue, and Iraq was one of them. This dissertation shows that Iraq was preoccupied first and foremost by its neighbors and the deep instabilities of the Middle East. Second, Baghdad was also fixated on regional concerns and extended its interests beyond the Arab world into the Horn of Africa. This work also traces the trajectory of Iraq’s relationship with its primary ally, the Soviet Union, and later, the Russian Federation. Moscow and Baghdad’s relationship was marred by mistrust and betrayal yet remained a matter of convenience for both even after the U.S.S.R.’s collapse. But no matter the tension, these two states could never fully walk away from one another. After two decades of uneasiness in their friendship, the Baʿthist regime and the successors to the Soviet Union, the Russian Federation, resumed relations in 1993, shortly after the dust had settled in Moscow. Given the exigencies of Iraq in the 1990s—isolated by a sanctions regime imposed at American initiative, but through U.N. auspices—Baghdad sought a political alliance with Moscow. Thanks to Russia’s seat on the U.N. Security Council, the Baʿthist regime believed Russia could bring tremendous benefit to an otherwise isolated and vulnerable Iraqi regime. This study joins recent works that show how smaller, and less powerful, states managed their statecraft in a time of ever-increasing complexity. These states were certainly caught up in events stemming from the U.S.-U.S.S.R. divide, but more often than not, these states had to confront internal frictions and intense regional rivalries first. In some instances, these states operated in other ideologies outside of the traditionally understood struggle of communism versus democratic capitalism. In the case of Iraq, pan-Arabism and, to a lesser extent, non-alignment played important roles in the formulation of Iraq’s foreign policy. Iraqi foreign policy must be understood through more than just the Iran-Iraq War (1980-1988), the First Gulf War (1990-1991), or the run-up to Operation IRAQI FREEDOM (2003-2011). Instead, the Baʿthist regime concentrated on three components during the period from 1968 to its April 2003 demise: 1) campaigns against its neighbors, Syria and Iran, 2) managing U.S.-U.S.S.R. relations as they connected to Iraq, especially due to oil and geopolitical concerns and 3) Iraq’s desire to lead the Arab world against Israel and the overreach of the superpowers into the Middle East. However, Iraqi foreign policy was complicated. Certainly, some exploits were driven to spite Iraq’s rivals, but this was not the key to all Iraqi foreign policy nor its main purpose. Rather, Iraq’s desire for autonomy in local, regional, and international environments drove its foreign policy initiatives. Through their embassy organizations, the Iraqis were able to extend their influence well beyond Iraq’s borders, reaching into a wide array of political, military, and diplomatic circles, Western and non-Western alike. Even the fall of the U.S.S.R. did not spell the end of Iraqi diplomatic scheming, nor did the chaotic aftermath of the First Gulf War stop Iraqi diplomatic machinations. In two case studies—Lebanon and East Africa—the Baʿth Party archives provide further detail than previously available to scholars. As a context for the pre-existing scholarship, the Baʿth documents provide scholars greater insight into Iraq’s commitments to pan-Arabism and a clearer sense of how actions like deploying “volunteer” forces in Lebanon were actually ways in which Saddam Hussein and the Baʿth Party elite could exercise further control over Iraqis and thus strengthen the party’s domestic security. These two cases connect the domestic, regional, and international commitments of Iraqi foreign policy in the Cold War era and beyond. This dissertation considers Iraqi foreign policy on Iraqi terms. It shows that the Iraqis had their own foreign policy interests free from superpower meddling or prodding. Iraq’s search for autonomy may disorient American ways of thinking about Iraqi foreign ambitions, but by considering Iraqi priorities first, scholars will have a better overall understanding of Iraqi military and diplomatic history.
Keywords: Iraq; Russia; USSR; Lebanon; Horn of Africa; Ba'th Party